Theorem on the argument of the almost periodic function of many variables - Perov, A.; Kibenko, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. И. Перов, А. В. Кибенко. Теорема об аргументе почти-периодической функции многих переменных A. Perovas, A. Kibenko. Teorema apie daugelio kintamųjų beveik periodinės funkcijos argumentą